Seismic risk reduction through retrofitting of school masonry buildings from Romania - Scupin, Alexandra; Văcăreanu, Radu (Frontiers in Built Environment, 2023)
Retrofitting the existing building stock is needed since it can cause significant losses for in case of damaging earthquake, particularly in structures used for public services, such as schools.Understanding that existing buildings might face severe damage in case of strong earthquakes and losses might not be acceptable in spaces used for public services, such as school buildings, leads to the conclusion that retrofitting the existing building stock must be considered. Effective and optimal seismic retrofitting measures applied to existing masonry constructions should arise from a strong understanding of the vulnerabilities associated with each structural typology and construction practice. Using representative structural configurations of the masonry buildings used in the education sector from Romania, the paper aims to evaluate the seismic risk associated to the existing buildings as well as to support informed decision making for seismic retrofitting measures. Starting from a broad database of the school masonry buildings, potential losses were evaluated considering two seismic hazard scenarios. For an earthquake having a 63% exceedance probability in 50 years, losses estimated for the education sector comprising masonry structures reach almost 240 mil. € and 2500 potential casualties. For highlighting that investments in retrofitting masonry structures from the education sector lead to significant reductions of potential losses, prioritization criteria were proposed and cost-benefit analysis were realized for about 15,000 buildings. Results are presented through graphs and maps that illustrate the distribution of annual failure probabilities at national level. Therefore, the methodology proposed and the results presented in this paper can represent a valuable tool for substantiating public policies aiming at reducing the seismic risk, in particular for existing masonry structures.